2020
DOI: 10.1109/jphot.2020.3005620
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Field of View in Visible Light Communication Systems for Intelligent Transportation Systems

Abstract: This paper reports a detailed experimental characterization of non Line-of-Sight (LoS) optical performances of a Visible Light Communication (VLC) system using a real traffic light for ultra-low latency, infrastructure-to-vehicle (I2V) communications for intelligent transportation systems (ITS) protocols. Despite the implementation of long-sought ITS protocols poses the crucial need to detail how the features of optical stages influence the overall performances of a VLC system in realistic configurations, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…It should be also mentioned that when the VLC receiver uses a rather narrow band-pass optical filter centered on the red wavelength, the effect of sunlight is significantly mitigated, which in turn generates a lower BER compared to a standard day scenario. A similar situation has been found in [ 22 ]. In this case, the experimental results also showed that the influence of the fluorescent lights is higher than the one of natural light.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…It should be also mentioned that when the VLC receiver uses a rather narrow band-pass optical filter centered on the red wavelength, the effect of sunlight is significantly mitigated, which in turn generates a lower BER compared to a standard day scenario. A similar situation has been found in [ 22 ]. In this case, the experimental results also showed that the influence of the fluorescent lights is higher than the one of natural light.…”
Section: Resultssupporting
confidence: 88%
“…In comparison, the V2V VLC system evaluated in [ 36 ], provided a communication distance of less than 20 m, whereas the system from [ 44 ] can deliver ranges up to 45 m. It should be pointed out here that the current research focused on automotive VLC systems is mainly orientated toward traffic Infrastructure-to-Vehicle (I2V) connections, as the VLC emitters developed based on transportation infrastructure elements (i.e., traffic lights, street lighting systems) have a significantly higher optical power, enabling longer communication distances. Even so, there are only few works [ 30 , 31 ] that report I2V-related VLC results with communication ranges above 75 m, whereas most of the existing systems provide communication distances of up to 50 m [ 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 ]. In this context, the 75 m communication range reported in this work provides important evidence that, step by step, the performances of automotive VLC systems are improving.…”
Section: Discussion On the Results Contributions Of This Work And Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen from Table 2, most of the I2V works [32]- [38] assume a single PD. Some of these [32], [35], [36] assume PD location at the front hood of the vehicle which is typically favorable for reception from traffic light while some [34], [37], [38] consider the top of the vehicle which is more suitable for reception from street lights. Such a single PD use can be justified in a single lane road with clear line-of-sight between the vehicle and the road side infrastructure.…”
Section: Commercialmentioning
confidence: 99%